Solid and Cystic Papillary Neoplasm of the Pancreas in a 18-Year-Old Female: A Case Report - Fakhry, Hussein; Abdelhady, Hosam (JOP. Journal of the Pancreas, 2013)
Context Solid and cystic papillary neoplasm of the pancreas is an extremely rare neoplasm that mostly affects young females in the mean age of 25 years and accounts for about 0.2-2.7% of all pancreatic tumors. Case report A 18-year-old female presented with progressively increasing mass in the left hypochondrium and epigastric regions and vague abdominal pain. There was no history of jaundice and vomiting. The mean diameter of the tumors was 17x24 cm. Preoperative core needle revealed solid and cystic papillary neoplasm. Distal pancreatectomy and splenectomy were performed. The patient did not receive adjuvant therapy and no tumor recurrence was detected in follow up. Conclusion Solid and cystic papillary neoplasm may reach large dimensions with a benign behavior and is curable by surgical excision. Differential diagnosis from other tumors with aggressive behavior is therefore important. Image: Pancreatic tumor with spleen.